Predictors of muslim’s intention to participate in takaful protection in Kedah - Nur Syahirah, Mansor (2021)
The Malaysian Takaful industry showed a positive growth in these recent years. More people have knowledge and more understand toward the Takaful protection. Nevertheless, there are few studies conducted specifically on the factors that influence Muslim’s intention to participate in Takaful protection in Kedah. The purpose to choose this study is to indicate the predictors that influence Muslim’s intention in order to participate in Takaful protection in Kedah. Three independent variables that used in this study to investigate the Muslim’s intention to participate in Takaful protection included product understanding, religious factor and attracting skills of Takaful agents. 385 set of questionnaires were distributed randomly in Kedah and the targeted Muslim respondents are household population. The obtained data were analyzed by using Pearson-correlation and Multiple Regressions. The finding was showing the independent variables are positively correlated with the Muslim’s intention to participate in Takaful protection. Product understanding of independent variable was the strongest predictor of Muslim’s intention to participate in Takaful protection. This considered to be as the contribution of this study. The findings were very useful for future researchers.